2006
DOI: 10.1074/jbc.m600171200
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation of Serine 492 of Perilipin A Directs Lipid Droplet Fragmentation and Dispersion

Abstract: Perilipin A is a key regulator of triacylglycerol storage and hydrolysis in adipocytes; phosphorylation of perilipin A by protein kinase A facilitates maximal lipolysis. Chronic stimulation of lipolysis in 3T3-L1 adipocytes causes large perinuclear lipid droplets to fragment into myriad dispersed perilipin A-covered microlipid droplets. In cultured fibroblasts stably expressing ectopic perilipin A, clustered lipid droplets disperse throughout the cytoplasm upon incubation of the cells with forskolin and isobut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
209
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(240 citation statements)
references
References 56 publications
20
209
0
1
Order By: Relevance
“…This interaction may facilitate access of LD-associated HSL to stored neutral lipid, thereby initiating lipolysis. While the present study was in review, Brasaemle and co-workers (43) reported that chronic PKA-dependent phosphorylation of Peri A induced LD remodeling (i.e. fragmentation and dispersion) independently of lipase action and suggested that this remodeling promoted lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction may facilitate access of LD-associated HSL to stored neutral lipid, thereby initiating lipolysis. While the present study was in review, Brasaemle and co-workers (43) reported that chronic PKA-dependent phosphorylation of Peri A induced LD remodeling (i.e. fragmentation and dispersion) independently of lipase action and suggested that this remodeling promoted lipolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the basal state, perilipin acts as a barrier to lipases, thereby maintaining a low rate of basal lipolysis. However, upon phosphorylation by PKA, perilipin facilitates the accessibility of lipases to lipid stores, thereby promoting lipolysis (Brasaemle et al 2000, Martinez-Botas et al 2000, Tansey et al 2001, Souza et al 2002, Zhang et al 2003, Marcinkiewicz et al 2006). In the current study, the mRNA level of HSL was increased, whereas the protein level of perilipin was decreased in Ad-DCD-injected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Another phenomenon that is ascribed to perilipin A is the appearance of microsized LDs after lipolytic stimulation (Marcinkiewicz et al 2006). Disruption of a sphere into many small spheres may be a mechanism to facilitate lipolysis by increasing the surface-to-volume ratio, but microsized LD formation has not been shown to correlate closely to release of lipolytic products (Bickel et al 2009), and seem to be generated in a region distant from the original LD (Yamaguchi et al 2007;Nagayama et al 2010).…”
Section: Structure and Function Of Lipid Dropletmentioning
confidence: 99%